Cleopatra rules! eaudiobook The amazing life of the original teen queen. - Shecter, Vicky Alvear (Recorded Books Inc., 2013)
Good. Evil. Dangerous. Glamorous. Will the real Cleopatra please stand up? Almost everything we know about the last queen of Egypt came from her enemies the Romans. Now it's time to meet the ''real'' Cleopatra, a ruler more complex, brilliant, and powerful than we ever knew. Cleopatra didn't just rock the boat when she became queen at seventeen. She rocked the world with brilliant alliances that kept her in power and in control. When Mark Antony tried to put Egypt under his thumb, she negotiated for - and won - more territory than any Egyptian ruler had snagged in generations. Cleopatra didn't just play by the rules. She made them up as she went along. She bowed to no one, including Octavian the future Caesar Augustus who never missed an opportunity to pump out anti-Cleopatra propaganda. The queen of Egypt has fascinated the world for thousands of years. It's time to find out why. So, on your knees, commoner! The world's most brilliant and outrageous queen - Cleopatra VII, the last Pharaoh of Egypt - is about to make her entrance. Includes maps, endnotes, timeline, glossary, sources, and index.